Systematic Dual Targeting of Dendritic Cell C-Type Lectin Receptor DC-SIGN and TLR7 Using a Trifunctional Mannosylated Antigen - Li, Rui-Jun Eveline; Hogervorst, Tim P.; Achilli, Silvia; Bruijns, Sven C.; Arnoldus, Tim; Vivès, Corinne; Wong, Chung C.; Thépaut, Michel; Meeuwenoord, Nico J.; van den Elst, Hans; Overkleeft, Herman S.; van der Marel, Gijs A.; et al. (Frontiers in Chemistry, 2019)
Dendritic Cells (DCs) are important initiators of adaptive immunity, and they possess a multitude of Pattern Recognition Receptors (PRR) to generate an adequate T cell mediated immunity against invading pathogens. PRR ligands are frequently conjugated to tumor-associated antigens in a vaccination strategy to enhance the immune response towards such antigens. One of these PPRs, DC-SIGN, a member of the C-type lectin receptor family, has been extensively targeted with Lewis structures and mannose glycans, often presented in multivalent fashion. We synthesized a library of well-defined mannosides (mono-, di- and tri-mannosides), based on known ‘high mannose’ structures, that we presented in a systematically increasing number of copies (n=1, 2, 3 or 6), allowing us to simultaneously study the effect of mannoside configuration and multivalency on DC-SIGN binding via surface plasmon resonance and flow cytometry. Hexavalent presentation of the clusters showed the highest binding affinity, with the hexa-α1,2-di-mannoside being the most potent ligand. The four highest binding hexavalent mannoside structures were conjugated to a model melanoma gp100-peptide antigen and further equipped with a Toll-like receptor 7 (TLR7)-agonist as adjuvant for DC maturation, creating a trifunctional vaccine conjugate. Interestingly, DC-SIGN affinity of the mannoside clusters did not directly correlate with antigen presentation enhancing properties and the α1,2-di-mannoside cluster with the highest binding affinity in our library even hampered T cell activation. Overall, this systematic study has demonstrated that multivalent glycan presentation can improve DC-SIGN binding but enhanced binding cannot be directly translated into enhanced antigen presentation and the sole assessment of binding affinity is thus insufficient to determine further functional biological activity. Furthermore, we show that well-defined antigen conjugates combining two different PRR ligands can be generated in a modular fashion to increase the effectiveness of vaccine constructs.